2011
DOI: 10.3892/ol.2011.511
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of IL-32 is a novel prognostic factor in patients with localized clear cell renal cell carcinoma

Abstract: Abstract. ) is a proinflammatory cytokine that acts as a significant pathogenetic factor in various diseases and malignancies. However, the clinical effect of IL-32 expression in renal cell carcinoma (RCC) has not previously been investigated. The aim of the present study was to examine the significance of IL-32 overexpression in localized clear cell RCC (CCRCC). We examined 112 patients with localized CCRCC who underwent nephrectomy. The clinicopathological data were obtained by retrospective review and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…IL-32 has also been proposed as a lung adenocarcinoma prognostic biomarker, in which high IL-32 expression was associated with high grade disease and metastasis incidence [24,25]. In clear cell renal cell carcinoma patients, IL-32 overexpression was associated with disease progression and poor overall survival, indicating that IL-32 may be a novel prognostic factor for predicting outcomes in this disease [26]. Similarly, IL-32 has been reported as a poor prognostic marker for gastric cancer [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…IL-32 has also been proposed as a lung adenocarcinoma prognostic biomarker, in which high IL-32 expression was associated with high grade disease and metastasis incidence [24,25]. In clear cell renal cell carcinoma patients, IL-32 overexpression was associated with disease progression and poor overall survival, indicating that IL-32 may be a novel prognostic factor for predicting outcomes in this disease [26]. Similarly, IL-32 has been reported as a poor prognostic marker for gastric cancer [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…There are 9 different splice variants in humans: IL-32α, IL-32β, [34][35][36][37][38] Chronic inflammation and autoimmune disease Elevated IL-32 level in chronic obstructive pulmonary disease (COPD), chronic rhinosinusitis (CRS), inflammatory bowel disease [9,13,39,40] Inflammatory bone disease Rheumatoid arthritis (RA), ankylosing spondylitis (AS), osteoporosis [3][4][5] IL-32γ, IL-32δ, IL-32ε, IL-32ξ, IL-32η, IL-32θ, and IL-32ζ [6], and different isoforms of IL-32 have diverse biological functions. IL-32 is now recognized as a proinflammatory cytokine produced in epithelial cells, NK cells, CD4 + T cells, and synovial fibroblasts in response to various cytokines such as IL-1β, tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), IL-6, IL-8, IL-12, and IL-18 [12][13][14].…”
Section: General Properties Of Il-32mentioning
confidence: 99%
“…IL-32 expression is also noted in hepatocellular carcinoma and pancreatic cancer [36,37]. Lee et al [38] demonstrated the significance of IL-32 as a novel prognostic factor in patients with localized clear cell renal cell carcinoma (CCRCC). The patients with elevated IL-32 expression are more likely to have high recurrence rates and low survival rates compared to individuals with low IL-32 expression.…”
Section: ) Il-32 In Infectious Diseasesmentioning
confidence: 99%
“…Although the receptor for IL-32 remains to be determined, IL-32 has been found to stimulate TNF-α, IL-1β and IL-8 production and thus act as a pro-inflammatory mediator in inflammatory diseases and tumor (7,10). IL-32 expression is increased in malignant esophageal tissues (11), and overexpression of IL-32 is reversely associated with 5-year recurrence-free, disease-specific and overall survival rates in localized clear cell renal cell carcinoma (12). However, the role of IL-32 in osteosarcoma progression remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%